Handbook of research on blockchain technology and the digitalization of the supply chain - Tharwa, Najar 1981-; Yousra, Najar 1980-; Aloui, Adel 1976- (IGI Global, 2023)
The book will present blockchain's basic concepts and pertinent methods that contributed to meet key supply chain management objectives such as supporting the digitalization process and electronic integration. It covers the issues inherent to most emergent topics and critical issues in blockchain adoption and diffusion from a supply chain perspective. It determines the current trends and challenges in the use of blockchain to enhance supply chain management. Moreover, the book defines solutions that hamper the adoption of blockchain in the supply chain field. It will be written for professionals who want to improve their understanding of the strategic role of this technology in improving problems related to fraud and trust in the supply chain
Keywords: Business logistics -- Technological innovations; Blockchains (Databases)